Understanding the relationship between the frequency of HbA1c monitoring, HbA1c changes over time, and the achievement of targets: a retrospective cohort study - Elton Mukonda; Diederick J. van der Westhuizen; Joel A. Dave; Susan Cleary; Luke Hannan; Jody A. Rusch; Maia Lesosky (BMC Endocrine Disorders)
Abstract Background The goal of post-diagnosis diabetes management is the achievement and maintenance of glycaemic control. Most clinical practice guidelines recommend 3–6 monthly HbA1c monitoring. Despite this guidance, there are few data supporting the impact of monitoring frequency on clinical outcomes, particularly from low- and middle-income country settings. This study evaluates the short-term impact of HbA1c monitoring intervals on changes in HbA1c levels, and the impact of adherence to monitoring recommendations on the achievement of HbA1c targets and HbA1c changes over time in a South African cohort. Research design and methods The study utilised routinely collected HbA1c test data on patients with diabetes aged ≥ 18 years in the Western and Northern Cape between 2015 and 2020. Two properties were calculated for each patient: the retest interval (the duration between consecutive HbA1c tests), and the monitoring adherence rate, which represents the proportion of retest intervals that met South Africa’s guideline recommendations. Mean changes in HbA1c by the retest interval were used to highlight the short-term impact of monitoring, while multistate modelling and linear mixed-effects modelling were then used to examine the effect of monitoring adherence on the achievement of glycaemic control targets and longitudinal changes in HbA1c. Results The 132,859 diabetes patients with repeat tests had a median of three HbA1c test requests, a median follow-up time of 2.3 years and a median retest interval of 10.3 months. A retest interval 2–4 months maximised the downward trajectory in HbA1c, while individuals with low adherence to the monitoring guidelines were the least likely to achieve glycaemic control in one year. Moreover, patients with low monitoring adherence had higher mean HbA1c levels compared to patients with moderate or high monitoring adherence. Conclusions The results from this study illustrate the importance of adherence to monitoring recommendations as adherent patients had better glycaemic control and lower mean HbA1c levels over time.